Effects of Country of Origin in Product Categories: A Study Concerning Italy and Great Britain - Elisa Rancati; Alessandro D’Agata (European Scientific Journal, ESJ, 2019)
This study examines country-of-origin in terms of the fit between two countries (Italy and Great Britain) and product categories. A framework is suggested which matches the importance of product category dimensions with the perceived image of the country-of-origin along the same dimensions. Such matches (or mismatches) can influence or not the customers in their decisionmaking process in a different manner concerning the country. Data collected from consumers in Italy and Great Britain demonstrate that strategic implications can increase sales in some category. This study has underlined the presence of an important domestic bias concerning convenience goods category, especially in food purchases. Instead, in specialty goods category, the customer seems to identify and prefer specific countries, and goods are critically evaluated for their origin.